A method for evaluating defects in dentin-resin bonding interface
By using an electron beam to bombard the dentin-resin bonding interface through scanning electron microscope, the problems of high false positive rate of defect detection of dentin-resin bonding interface in the prior art, many factors affecting artificial aging, strong subjectiveness of naked eye recognition, and high cost of nanoindentation are solved, and direct, fast and intuitive defect positioning detection is achieved.
Patent Information
- Application Number
- CN202210135252.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-14
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-02-14
AI Technical Summary
In the prior art, the dentin-resin bonding interface defect detection has problems such as high false positive rate of dye impregnation, many factors affecting artificial aging, strong subjectiveness of naked eyes and high cost of nanoindentation.
The incident electron beam emitted by scanning electron microscope bombards the dentin-resin bonding interface, gradually increasing the electron beam voltage, causing the weak interface and defective parts to be damaged, thereby realizing the positioning detection of defects in the dentin-resin bonding interface.
The direct, fast and intuitive dentin-resin bonding interface defect positioning detection is achieved, avoiding the occurrence of false positive and false negative results, reducing the subjectivity and operational sensitivity of the detection, and the loss of material equipment is extremely small.
Smart Images

Figure CN114624469B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oral bonding and restoration, and relates to a method for evaluating dentin bonding interface defects, and specifically to a method for evaluating dentin-resin bonding interface defects. Background Art
[0002] The detection of dentin-resin bonding interface defects is a very important evaluation item when studying the effect of dental bonding. At present, the detection of dentin-resin bonding interface defects mainly relies on indirect means, such as nanoleakage and microleakage detection.
[0003] Traditional nano-leakage and micro-leakage are achieved by aging the sample to cause interface damage, then dyeing it to allow the dye to penetrate into the damaged and loose interface, and then observing it under an optical or electron microscope to evaluate the interface defects.
[0004] However, traditional technologies have great shortcomings. First, interface damage is displayed by dye impregnation, which is an indirect method. Dye impregnation may contaminate other parts where no leakage occurs, resulting in false positive results. Second, interface microleakage is created by artificial aging. Interface defects further expand during aging, forming interface micro-gaps. Although there are many types of artificial aging, they are different from the actual situation in the human mouth, and there are many uncontrollable factors in the aging process, which leads to false positive and false negative test results. Therefore, it is of practical significance to seek an evaluation method that directly displays defects in the dentin-resin bonding interface.
[0005] The existing direct observation method is to magnify the dentin-resin bonding interface under a scanning electron microscope or a transmission electron microscope, carefully distinguish each field of view, and check the quality of the interface mixed layer and the size of the resin protrusion with the help of the examiner's experience. This method is not only time-consuming and laborious, but also extremely dependent on the examiner's personal experience and is highly subjective.
[0006] In the prior art, there is also a method of testing the nanomechanical properties of the dentin-resin bonding interface by using an atomic force microscope in combination with nanoindentation technology. This method displays the areas with poor mechanical strength of the interface in the form of a performance parameter heat map, which is the defects and weaknesses of the interface. However, in this method, the acquisition of the heat map requires a large amount of nanoindentation data, which is extremely time-consuming and causes great loss to the nanoindenter. In addition, the resolution of the atomic force microscope is lower than that of the electron microscope, making it difficult to perfectly integrate the morphology and mechanical strength results. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for evaluating dentin-resin bonding interface defects, which can realize the positioning detection of dentin-resin bonding interface defects in a simpler, faster and more intuitive way, and solve the problems of high false positive rate of dye staining, too many factors affecting artificial aging, strong subjectivity and operation sensitivity of naked eye identification, and high time-consuming and costly nanoindentation.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions to achieve it.
[0009] The present invention utilizes an incident electron beam emitted by a scanning electron microscope to bombard the dentin-resin bonding interface under the observation field of view, and by gradually increasing the electron beam voltage and increasing the bombarding electron beam energy, the weak and defective parts of the dentin-resin bonding interface are damaged, thereby realizing the positioning detection of the defects of the dentin-resin bonding interface.
[0010] The method for evaluating dentin-resin bonding interface defects of the present invention comprises the following steps:
[0011] Step 1, preparing dentin-resin observation samples;
[0012] Step 2, setting observation parameters of a scanning electron microscope, bombarding the dentin-resin bonding interface of the observation sample prepared in step 1 with an electron beam emitted by the scanning electron microscope, so that the defective part of the dentin-resin bonding interface is damaged;
[0013] Step 3, observing the damaged part through a scanning electron microscope to locate the dentin-resin bonding interface defect, thereby realizing the positioning detection of the dentin-resin bonding interface defect.
[0014] Preferably, the electron beam bombardment observation of the dentin-resin bonding interface of the sample in step 2 is achieved by the following method: after setting the observation parameters of the scanning electron microscope, the current setting is kept unchanged, and the acceleration voltage is gradually increased from 5kV to 30kV, with each 2-5kV as a gradient.
[0015] Preferably, the initial acceleration voltage of the scanning electron microscope in step 2 is 5 kV.
[0016] Preferably, the magnification of the scanning electron microscope in step 2 is greater than 1000 times.
[0017] Preferably, the preparation of the dentin-resin scanning electron microscope observation sample in step 1 comprises the following sub-steps:
[0018] Sub-step 1: Sample preparation: preparation of dentin-resin bonding specimens;
[0019] Sub-step 2: sample cutting: cutting the dentin-resin bonding sample into dentin-resin bonding sheets along a direction perpendicular to the bonding interface;
[0020] Sub-step 3: Sample fixation: The dentin-resin bonding piece was rinsed with deionized water, fixed with glutaraldehyde fixative, and then rinsed again with deionized water;
[0021] Sub-step 4: mirror polishing: mirror polishing the observation surface of the dentin-resin bonding sheet, and after polishing, use an ultrasonic cleaner to vibrate and clean the dentin sheet;
[0022] Sub-step 5: ethanol gradient dehydration: the mirror-polished dentin-resin bonding sheet is immersed in ethanol aqueous solutions with volume fractions of 30%, 50%, 70%, 80%, and 95% in sequence for dehydration, and then immersed in anhydrous ethanol for dehydration twice;
[0023] Sub-step 6: tert-butanol drying: the dentin-resin bonding sheet after gradient ethanol dehydration is soaked in a tert-butanol ethanol solution with a volume fraction of 75%, and then soaked in anhydrous tert-butanol at a temperature above 26°C. After replacing the anhydrous tert-butanol, the sample is completely condensed and solidified in an environment of 0-4°C and then dried;
[0024] Sub-step 7: Sample bonding and gold spraying: The dried dentin-resin bonding sheet is fixed on a metal sample stage and gold sprayed using a coating apparatus to obtain a dentin-resin scanning electron microscope observation sample for scanning electron microscope observation.
[0025] Further preferably, in said sub-step 2, the thickness of the cut dentin-resin bonding sheet is 1.5 mm.
[0026] Further preferably, in the sub-step 3, the temperature of the glutaraldehyde fixative is 4° C., and the sample fixation time is 24 hours.
[0027] Further preferably, in the sub-step 5, the soaking and dehydration time in the ethanol-water solution is 10-15 min, and the soaking and dehydration time in the anhydrous ethanol is 10-15 min.
[0028] Further preferably, in the sub-step 6, the soaking time in the tert-butanol ethanol solution is 10-15 min, and the soaking time in the anhydrous tert-butanol is 10-15 min.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention eliminates the steps of dyeing and artificial aging, avoids the false positive and false negative results caused by dye overflow and misoperation, and achieves direct observation and analysis of the interface.
[0031] 2. Compared with the method of inspecting one by one with the naked eye under a microscope, the defective structure can be well displayed in the image because it is destroyed, thus avoiding errors caused by personal factors of the observer to a certain extent.
[0032] 3. Compared with nanoindentation technology, the electron beam can bombard the interface in a few minutes, and at the same time obtain the morphological position information of the damaged interface defect part, which is simple and fast, and the loss of materials and equipment is extremely small. In addition, the interface morphology features collected by the scanning electron microscope in the present invention are clearer and easier to identify than those collected by the atomic force microscope. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] Figure 1 This is the observation picture of the immediate bonding interface of single bond dentin;
[0035] Figure 2 This is the observation picture of the bonding interface of single bond dentin aging;
[0036] Figure 3 The diagram is a diagram of the pressure increase process of the instant bonding interface of the single bond dentin adhesive of the embodiment;
[0037] Figure 4 This is an example of an adhesive single bond dentin immediate bonding multiple interface observation diagram;
[0038] Figure 5 This is an observation diagram of multiple interfaces of single bond bonding of aging dentin. DETAILED DESCRIPTION
[0039] The embodiments of the present invention will be described in detail below with reference to examples, but those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.
[0040] The method for evaluating dentin-resin bonding interface defects of the present invention comprises the following steps:
[0041] Step 1, preparing dentin-resin observation samples;
[0042] The preparation was carried out according to the conventional dentin bonding interface scanning electron microscope observation sample preparation requirements. The specific process is as follows:
[0043] Sub-step 1: Sample preparation: preparation of dentin-resin bonding specimens;
[0044] Sub-step 2: Sample cutting: Using a low-speed cutter and a diamond blade, under water cooling, cut the dentin-resin bonded sample into a dentin-resin bonded sheet with a thickness of 1.5 mm in a direction perpendicular to the bonding interface;
[0045] Sub-step 3 Sample fixation: The dentin-resin bonding piece was rinsed with deionized water for 5-10 minutes, then fixed with glutaraldehyde fixative (4°C) for 24 hours, and then rinsed again with deionized water for 5-10 minutes;
[0046] Sub-step 4: Mirror polishing: Use a small grinder, a wool polishing head, and diamond abrasive paste to mirror-polish the observation surface of the dentin-resin bonding sheet. First, use water sandpaper to polish step by step in the order of 400 mesh, 2000 mesh, 3000 mesh, 4000 mesh, and 5000 mesh. Then use diamond abrasive paste in the order of 6000 mesh (W1.5), 8000 mesh (W1), and 10000 mesh (W0.5), in conjunction with a wool polishing wheel and a small grinder, to polish the bonding interface of the dentin-resin bonding sheet step by step to a mirror effect. During this process, the dentin-resin bonding sheet is always kept moist. After polishing, use an ultrasonic cleaner to vibrate and clean the dentin-resin bonding sheet for 5 minutes;
[0047] Sub-step 5: ethanol gradient dehydration: the mirror-polished dentin-resin bonding sheet is immersed in ethanol aqueous solutions with volume fractions of 30%, 50%, 70%, 80%, and 95% for dehydration for 10-15 minutes, and then immersed in anhydrous ethanol for dehydration twice, each time for 10-15 minutes;
[0048] Sub-step 6: tert-butanol drying: the dentin-resin bonding sheet after ethanol gradient dehydration is soaked in a tert-butanol ethanol solution with a volume fraction of 75% for 10-15 minutes, and then soaked in anhydrous tert-butanol at above 26°C for 10-15 minutes. After replacing the anhydrous tert-butanol, the sample is placed in a refrigerator at 0-4°C to completely condense and solidify, and then placed in a vacuum dryer or a vacuum evaporation coating instrument to completely dry the dentin-resin bonding sheet;
[0049] Sub-step 7: Sample bonding and gold spraying: The dried dentin-resin bonding sheet is fixed on the metal sample stage using conductive tape or glue. After gold spraying by the coating instrument, a dentin-resin scanning electron microscope observation sample is obtained for scanning electron microscope observation.
[0050] Step 2, setting observation parameters of a scanning electron microscope, bombarding the dentin-resin bonding interface of the observation sample prepared in step 1 with an electron beam emitted by the scanning electron microscope, so that the defective part of the dentin-resin bonding interface is damaged;
[0051] The working principle of the scanning electron microscope is as follows: the electron beam emitted by the electron gun is focused and converged into a point light source; the point light source forms a high-energy electron beam under the acceleration voltage; the high-energy electron beam is focused into a light spot with a tiny diameter through two electromagnetic lenses. After passing through the last level of electromagnetic lens with a scanning coil, the electron beam bombards the sample surface point by point in a raster scanning manner, and stimulates electronic signals at different depths. At this time, the electronic signal will be received by the probes of different signal receivers above the sample, and synchronously transmitted to the computer display through the amplifier to form a real-time imaging record. The acceleration voltage of the scanning electron microscope is a symbol of the energy of the electron beam. The greater the acceleration voltage, the greater the energy of the electron beam, the greater the penetration of the sample surface, and the sample is damaged by collision and heating.
[0052] Using the above principle, by gradually increasing the acceleration voltage of the electron beam of the scanning electron microscope, its energy is increased. The dentin-resin bonding interface defect, as the weakest structure, will be damaged first under the bombardment of the high-energy electron beam. The bombarded and damaged dentin-resin bonding interface defect will undergo characteristic changes such as darkening of color and structural collapse, thereby achieving the positioning observation of the dentin-resin bonding interface defect.
[0053] Specifically, the observation parameters of a conventional field emission scanning electron microscope are set, and the initial acceleration voltage is set to 5 kV. The magnification is adjusted according to the needs, and generally should be more than 1000 times, otherwise the details of the bonding interface structure cannot be clearly identified.
[0054] When the electron beam bombards the dentin-resin bonding interface, the current setting remains unchanged, and the acceleration voltage is gradually increased from about 5kV to 30kV, with a gradient of 2-5kV. The boost gradient and the final voltage value can be adjusted according to the changes in the sample morphology. Samples prepared with different bonding materials can tolerate different electron beam energies, and this is used to evaluate the quality of the bonding interface. That is, the better the interface quality and the fewer defects, the higher the energy of the electron beam that can be tolerated.
[0055] Step 3, observing the damaged part through a scanning electron microscope to locate the dentin-resin bonding interface defect, thereby realizing the positioning detection of the dentin-resin bonding interface defect.
[0056] The damaged dentin-resin bonding interface defect sites will undergo characteristic changes such as darkening of color and structural collapse, thereby achieving the location observation and detection of dentin-resin bonding interface defects.
[0057] Specifically, the dentin-resin observation samples were prepared using the acid-etching-rinsing adhesive 3M single bond 2 and 3M Z250 resin, and then the dentin-resin bonding interface was observed using a scanning electron microscope. Figure 1, is the observation picture of the immediate bonding interface of single bond dentin. Figure 1 The middle left picture shows the morphology of the dentin-resin bonding interface under the standard accelerating voltage of 5kV observed by scanning electron microscopy, and the right picture shows the morphology observed after increasing the accelerating voltage to 15kV. It can be seen that the structure at the bottom of the mixed layer has collapsed and darkened (white arrow), while other parts have not changed significantly. It can be seen that in this field of view, the defect of the dentin-resin bonding interface is the structure in the yellow box at the bottom of the mixed layer. During the voltage increase from 5kV to 10kV, no obvious damage to the dentin-resin bonding interface was observed, and 15kV was determined to be the critical voltage value for the dentin-resin bonding interface defects to be destroyed by the electron beam. From the observation results in the figure, the defects of the dentin-resin bonding interface are concentrated at the bottom of the mixed layer, which is consistent with the previous research reports on the bonding formation mechanism that the weak interface of the acid-etching-rinsing adhesive is located at the bottom of the mixed layer. For acid-etching and rinsing adhesives, due to the inconsistency between the degree of acid etching and the penetration depth of the bonding resin, there will be some exposed collagen at the bottom of the mixed layer that is not wrapped by the resin penetration, which becomes the weak point of the dentin-resin bonding interface. The weak point will further develop and debond, and form nano-leakage and micro-leakage.
[0058] The bonding specimens were prepared using the same bonding material and tooth tissue. The results of scanning electron microscopy observation of the dentin-resin bonding interface after 5000 hot and cold cycle aging were as follows: Figure 2 shown. Figure 2 This is an observation diagram of the bonding interface of single bond dentin aging. Figure 2 The middle left picture shows the morphology of the resin-dentin bonding interface observed by scanning electron microscopy at a standard accelerating voltage of 5kV. Figure 2 The middle right picture shows the morphology observed after increasing the acceleration voltage to 10 kV. It can be seen that some structures at the bottom of the mixed layer have collapsed and darkened in color (white arrows), while other parts have not changed significantly. This shows that in this field of view, the defect of the dentin-resin bonding interface is the structure within the white arrow at the bottom of the mixed layer. Compared with the immediate bonding interface formed by the same bonding material, the critical voltage value for the damage of the aged dentin-resin bonding interface defect is lower, only 10 kV. At 15 kV, more structures at the bottom of the mixed layer collapsed and darkened in color. The above phenomenon shows that after aging, the quality of the resin-dentin bonding interface has significantly decreased. Under the same acceleration voltage electron beam bombardment, more defects appeared in the dentin-resin bonding interface.
[0059] The experimental results show that this method can directly display the defects of the resin-dentin bonding interface under the field of view of a scanning electron microscope without artificially creating nanoleakage and microleakage, and use this to evaluate the quality of the dentin-resin bonding interface. The higher the interface quality, the greater the electron beam energy that can be tolerated, and the higher the interface quality, the less interface damage displayed under the same energy electron beam bombardment.
[0060] Example 1 Observation of defects at the dentin-resin bonding interface of 3M singlebond etch-rinse adhesive
[0061] Step 1: Prepare dentin-resin observation samples.
[0062] 1. Sample preparation: Preparation of dentin-resin bonding samples;
[0063] 2 Sample cutting: Use a low-speed cutter and diamond blade, under water cooling, to cut the specimen into dentin-resin bonding sheets of about 1.5 mm in the direction perpendicular to the bonding interface;
[0064] 3 Sample fixation: The dentin-resin adhesive sheet was rinsed with deionized water for 8 minutes, then fixed with glutaraldehyde fixative (4°C) for 24 hours, and then rinsed again with deionized water for 8 minutes;
[0065] 4 Mirror polishing: Use a small grinder, a wool polishing head and diamond paste to mirror polish the observation surface of the dentin-resin bonding sheet. First, use water sandpaper to polish step by step in the order of 400 mesh, 2000 mesh, 3000 mesh, 4000 mesh, and 5000 mesh. Then use diamond paste in the order of 6000 mesh (W1.5), 8000 mesh (W1), and 10000 mesh (W0.5), in conjunction with a wool polishing wheel and a small grinder, to polish the bonding interface of the dentin-resin bonding sheet step by step to a mirror effect. During this process, the dentin-resin bonding sheet is always kept moist. After polishing, use an ultrasonic cleaner to vibrate and clean the dentin-resin bonding sheet for 5 minutes;
[0066] 5. Ethanol gradient dehydration: The dentin-resin bonding sheet was immersed in 30%, 50%, 70%, 80%, and 95% ethanol aqueous solutions for 15 minutes, and then immersed in anhydrous ethanol for 2 times, each time for 15 minutes.
[0067] 6 Tert-butanol drying: After gradient dehydration with ethanol, the dentin-resin bonding sheet is soaked in a tert-butanol ethanol solution with a volume fraction of 75% for 10-15 minutes, and then soaked in anhydrous tert-butanol for 10-15 minutes at a temperature above 26°C. After replacing the anhydrous tert-butanol, the sample is placed in a refrigerator at 0-4°C to completely condense and solidify, and then placed in a vacuum dryer or vacuum evaporation coating apparatus to completely dry the dentin-resin bonding sheet;
[0068] 7. Gold spraying on the adhesive sample: The dried dentin-resin adhesive sheet is fixed on the metal sample stage using conductive tape or glue. After gold spraying by the coating instrument, the dentin-resin scanning electron microscope observation sample is obtained for scanning electron microscope observation.
[0069] Step 2, setting observation parameters of a scanning electron microscope, bombarding the dentin-resin bonding interface of the observation sample prepared in step 1 with an electron beam emitted by the scanning electron microscope, so that defective parts of the dentin-resin bonding interface are damaged.
[0070] The initial acceleration voltage of the field emission scanning electron microscope was set to 5 kV. A suitable field of view was selected under a low-power microscope, requiring the interface to be clear and flat with less contamination. After selection, the magnification was adjusted to 5000 times, and the working distance was about 8 mm.
[0071] The scanning electron microscope keeps the current setting unchanged, and the acceleration voltage gradually increases from about 5kV to 20kV, with each 5kV as a gradient. The image acquisition voltage is 5kV, and the image brightness and contrast are kept consistent as much as possible. Therefore, the entire voltage change process is: 5kV observation → 10kV bombardment → 5kV observation → 15kV bombardment → 5kV observation → 20kV bombardment → 5kV observation, such as Figure 3 As shown, a total of 4 photos of dentin-resin bonding interface defect observation were obtained;
[0072] Step 3, observing the damaged part through a scanning electron microscope to locate the dentin-resin bonding interface defect, thereby realizing the positioning detection of the dentin-resin bonding interface defect.
[0073] Dentin-resin bonding interface defects that have been bombarded by electron beams and damaged appear as darkening and structural collapse in the field of view of scanning electron microscopy, such as Figure 3 As shown in FIG. 1 , the pressure increase process of the instant bonding interface of the single bond dentin adhesive of the embodiment is shown. Figure 3In the figure, there was no obvious change in the dentin-resin bonding interface after 10kV bombardment, but after 15kV bombardment, structural morphological changes occurred at the bottom of the mixed layer in the middle of the field of view, which was the location of the dentin-resin bonding interface defect. After 20kV bombardment, the range of defects in the dentin-resin bonding interface was further expanded, and there were obvious structural morphological changes at the bottom of the interface mixed layer in the entire field of view. It can be concluded that for this bonding sample, 15kV is the critical voltage value for observing dentin-resin bonding interface defects. At this voltage, multiple dentin-resin bonding interfaces were randomly selected for sampling and observation, and the quality of the dentin-resin bonding interface was evaluated by calculating the number of defect sites and range ratio. Figure 4 As shown in the figure, the single bond adhesive in the embodiment of the present invention is used to observe multiple interfaces of dentin for immediate bonding. In this embodiment, a total of 4 interfaces are selected, and only one interface undergoes local structural morphological changes under 15kV electron beam bombardment ( Figure 3 and Figure 4 ).
[0074] Prepare aging specimens of bonding samples from the same tooth and observe and analyze them using the above method. Figure 5 The following are observation pictures of multiple interfaces of aged dentin bonding with the adhesive single bond of the embodiment. It can be seen that under the bombardment of 15kV electron beam, local structural morphological changes occurred in the three selected dentin-resin bonding interfaces, and the range was significantly larger than that of the immediate sample.
[0075] Although the present invention has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for evaluating dentin-resin bonding interface defects, characterized in that: The following steps are involved: Step 1, preparation of dentin-resin observation samples, including the following sub-steps: Sub-step 1: Sample preparation: preparation of dentin-resin bonding specimens; Sub-step 2: sample cutting: cutting the dentin-resin bonding sample into dentin-resin bonding sheets along a direction perpendicular to the bonding interface; Sub-step 3: Sample fixation: The dentin-resin bonding piece was rinsed with deionized water, fixed with glutaraldehyde fixative, and then rinsed again with deionized water; Sub-step 4: mirror polishing: mirror polishing the observation surface of the dentin-resin bonding sheet, and after polishing, using an ultrasonic cleaning machine to vibrate and clean the dentin-resin bonding sheet; Sub-step 5: ethanol gradient dehydration: the mirror-polished dentin-resin bonding sheet is immersed in ethanol aqueous solutions with volume fractions of 30%, 50%, 70%, 80%, and 95% in sequence for dehydration, and then immersed in anhydrous ethanol for dehydration twice; Sub-step 6: tert-butanol drying: the dentin-resin bonding sheet after gradient ethanol dehydration is soaked in a tert-butanol ethanol solution with a volume fraction of 75%, and then soaked in anhydrous tert-butanol at a temperature above 26°C. After replacing the anhydrous tert-butanol, the sample is completely condensed and solidified in an environment of 0-4°C and then dried; Sub-step 7: Sample bonding and gold spraying: The dried dentin-resin bonding sheet is fixed on a metal sample stage, and gold sprayed using a coating apparatus to obtain a dentin-resin scanning electron microscope observation sample for scanning electron microscope observation; Step 2, setting observation parameters of a scanning electron microscope, bombarding the dentin-resin bonding interface of the observation sample prepared in step 1 with an electron beam emitted by the scanning electron microscope, so that the defective part of the dentin-resin bonding interface is damaged; Step 3, observing the damaged part through a scanning electron microscope to locate the dentin-resin bonding interface defect, thereby realizing the positioning detection of the dentin-resin bonding interface defect.
2. The method for evaluating dentin-resin bonding interface defects according to claim 1, characterized in that: In step 2, the electron beam bombardment observation of the dentin-resin bonding interface of the sample is achieved by the following method: After setting the observation parameters of the scanning electron microscope, keep the current setting unchanged, and gradually increase the acceleration voltage from 5 kV to 30 kV, with a gradient of 2-5 kV.
3. The method for evaluating dentin-resin bonding interface defects according to claim 1, characterized in that: The initial acceleration voltage of the scanning electron microscope in step 2 is 5 kV.
4. The method for evaluating dentin-resin bonding interface defects according to claim 1, characterized in that: The magnification of the scanning electron microscope in step 2 is greater than 1000 times.
5. The method for evaluating dentin-resin bonding interface defects according to claim 1, characterized in that: The thickness of the dentin-resin bonding sheet cut in the sub-step 2 is 1.5 mm.
6. The method for evaluating dentin-resin bonding interface defects according to claim 1, characterized in that: In the sub-step 3, the temperature of the glutaraldehyde fixative is 4° C., and the sample is fixed for 24 hours.
7. The method for evaluating dentin-resin bonding interface defects according to claim 1, characterized in that: In the sub-step 5, the soaking and dehydration time of the ethanol-water solution is 10-15 minutes, and the soaking and dehydration time of the anhydrous ethanol is 10-15 minutes.
8. The method for evaluating dentin-resin bonding interface defects according to claim 1, characterized in that: In the sub-step 6, the soaking time in the tert-butanol ethanol solution is 10-15 minutes, and the soaking time in the anhydrous tert-butanol is 10-15 minutes.
Citation Information
Patent Citations
Failure point positioning method and chip failure analysis method
CN105842264A